Observation of two new excited Ξ0 b states decaying to Λ0b K- π+ - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Frau, Giulia; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Kopecná, Renata; et al. (Physical review letters, 2022)
Two narrow resonant states are observed in the Λ0bK−π+ mass spectrum using a data sample of proton-proton collisions at a center-of-mass energy of 13 TeV, collected by the LHCb experiment and corresponding to an integrated luminosity of 6 fb−1. The minimal quark content of the Λ0bK−π+ system indicates that these are excited Ξ0b baryons. The masses of the Ξb(6327)0 and Ξb(6333)0 states are m[Ξb(6327)0]=6327.28+0.23−0.21±0.12±0.24 and m[Ξb(6333)0]=6332.69+0.17−0.18±0.03±0.22 MeV, respectively, with a mass splitting of Δm=5.41+0.26−0.27±0.12 MeV, where the uncertainties are statistical, systematic, and due to the Λ0b mass measurement. The measured natural widths of these states are consistent with zero, with upper limits of Γ[Ξb(6327)0]<2.20(2.56) and Γ[Ξb(6333)0]<1.60(1.92) MeV at a 90% (95%) credibility level. The significance of the two-peak hypothesis is larger than nine (five) Gaussian standard deviations compared to the no-peak (one-peak) hypothesis. The masses, widths, and resonant structure of the new states are in good agreement with the expectations for a doublet of 1D Ξ0b resonances.
The LHCb Collaboration: R. Aaij, F Archilli, S. Bachmann, D. Berninghoff, M. Borsato, G. Frau, J.P. Grabowski, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, R. Kopecna, B. Leverington, P. Li, J. Marks, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, A. Zhelezov [und viele weitere]
Gesehen am 11.07.2022
Im Titel sind "0", "+" und "-" jeweils hochgestellt, "b" ist jeweils tiefgestellt